Penerapan Media Sosial YouTube Dalam Meningkatkan Mahārah Al-Istimā’ Siswa Kelas VII SMP IT Al Insyirah Kota Makassar - Isnaeni S; Qahar Zainal, Abdul; Wahab, Abdul; Wahyudin; Farida, Nur; Ansar (Universitas Islam Negeri Alauddin, 2023)
The aim of this research is to determine the implementation of YouTube social media in Arabic language lessons for 7th-grade female students at SMP IT Al Insyirah in Makassar City and to assess the application of YouTube social media in enhancing the listening skills of these students. The research method used in this study is Classroom Action Research using the Kurt Lewin model, which consists of two cycles, with each cycle comprising one or more meetings. The sample for this research consists of 10 female students from the 7th grade at SMP IT Al Insyirah in Makassar City. Data collection techniques include observation, tests, and documentation. The tests include both pre-tests and post-tests. The pre-test is conducted at the beginning of the session before students receive treatment or engage in the learning process involving the use of YouTube social media. The post-test is conducted at the end of each meeting in each cycle. Data analysis techniques involve using percentage calculation formulas and mean values for the analysis of the improvement in listening skills. The results of this research indicate that the implementation of YouTube social media in Arabic language lessons led to an improvement in the listening skills of 7th-grade female students at SMP IT Al Insyirah from the pre-cycle to cycle II. According to the test results conducted during the learning process in the classroom, the pre-cycle average score was 29%, the cycle I average score increased to 68%, and the cycle II average score was 90.5%. Based on these findings, it can be concluded that the application of YouTube social media in each cycle contributes to a significant enhancement in listening skills with a category of excellent.